Recycling nitrogen from liquid digestate via novel reactive struvite and zeolite minerals to mitigate agricultural pollution. (March 2023) - Galamini, Giulio; Ferretti, Giacomo; Rosinger, Christoph; Huber, Sabine; Medoro, Valeria; Mentler, Axel; Díaz-Pinés, Eugenio; Gorfer, Markus; Faccini, Barbara; Keiblinger, Katharina Maria
Abstract: Recycling nutrients is of paramount importance. For this reason, struvite and nitrogen enriched zeolite fertilizers produced from wastewater treatments are receiving growing attention in European markets. However, their effects on agricultural soils are far from certain, especially struvite, which only recently was implemented in EU Fertilizing Product Regulations. In this paper, we investigate the effects of these materials in acid sandy arable soil, particularly focusing on N dynamics, evaluating potential losses, transformation pathways, and the effects of struvite and zeolitic tuffs on main soil biogeochemical parameters, in comparison to traditional fertilization with digestate. Liming effect (pH alkalinization) was observed in all treatments with varying intensities, affecting most of the soil processes. The struvite was quickly solubilized due to soil acidity, and the release of nutrients stimulated nitrifying and denitrifying microorganisms. Zeolitic tuff amendments decreased the NOx gas emissions, which are precursors to the powerful climate altering N2 O gas, and the N enriched chabazite tuff also recorded smaller NH3 emissions compared to the digestate. However, a high dosage of zeolites in soil increased NH3 emissions after fertilization, due to pronounced pH shifts. Contrasting effects were observed between the two zeolitic tuffs when applied as soil amendments; while the chabazite tuff had a strong positive effect – increasing up to ∼90% the soil microbial N immobilization – the employed clinoptilolite tuff had immediate negative effects on the microbial biomass, likely due to the large quantities of sulphur released. However, when applied at lower dosages, the N enriched clinoptilolite also contributed to the increase of microbial N. From these outcomes, we confirm the potential of struvite and zeolites to mitigate the outfluxes of nutrients from agricultural systems. To gain the best results and significantly lower environmental impacts, extension practitioners could give recommendations based on the soils that are planned for zeolite application. Graphical abstract: Image 1 Highlights: Soil pH control is crucial for struvite, zeolite and digestate best uses. Zeolites mitigated soil NOx emissions. Chabazite zeolite increased the assimilation of N by soil microorganisms. The S released from the clinoptilolite tuff induced microbial toxicity. Alkalinization increased NH3 soil losses, SOM dispersion and struvite dissolution.